Contrastive Analysis of Arabic and Javanese (Ngapak) Phonology in Student Conversation at the Darussalam Islamic Boarding School in Purwokerto - Mahmudah, Uswatun; Triyana (International Proceedings of Nusantara Raya, 2022)
This study was conducted to analyze and describe a student's pronunciation between Arabic and Javanese (ngapak) at at the Darussalam Islamic boarding school in Purwokerto which was explored using the methods of observation, interviews, and documentation. This data aims to compare the sound system of Arabic and Javanese (ngapak) in Arabic conversation because it causes differences and similarities to the two languages ​​so that using contrastive analysis because the majority of students are from Java so that the accent in speaking Arabic is still attached to the Javanese accent. The researcher conducted an in-depth analysis so that the data obtained could be evaluated using the right method, namely the introduction of hijaiyah letters according to the Arabic dialect so that the researcher's goal was to lead students to be able to pronounce Arabic according to good rules.